Kelayakan Media Puzzle Suku Kata dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Silmi Triana; Ndaru Mukti Oktaviani; Yani Fitriyani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The lack of variation in learning media in Indonesian language learning causes students to be less focused and less enthusiastic during the learning process. This condition indicates the need for learning media that is interesting and appropriate to the characteristics of elementary school students. One alternative that can be used is syllable puzzle media, which is able to present learning in a more concrete and interactive way. This study aims to develop syllable puzzle media in Indonesian language learning for second-grade elementary school students. The type of research used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The data collection technique used validation sheets given to media experts and material experts to determine the feasibility level of the developed media. The validation results showed that the syllable puzzle media met the criteria for appropriate use in learning. Therefore, the syllable puzzle media can be used as an alternative learning medium for Indonesian language learning that is interesting, interactive, and suitable for the characteristics of second-grade elementary school students.